ANALISIS PASAL 100 UNDANG – UNDANG NOMOR 1 TAHUN 2023 TENTANG HUKUMAN MATI BERSYARAT BERDASARKAN ASAS KEADILAN DAN ASAS KEPASTIAN HUKUM - Indah lestari; Kusuma, Putu Riski Ananda; hartono, made sugi; Dewa Bagus Sanjaya (Jurnal Ilmu Hukum Sui Generis, 2024)
This study aims (1) to find out and analyze how the mechanism for implementing the death penalty according to current regulations in Indonesia, (2) to find out the inhibiting factors in the implementation of the death penalty after the judge's decision. The type of research used by researchers is normative legal research, namely through a statutory approach, and a conceptual approach. The sources of legal materials used are the 1945 Constitution, Presidential Regulation, and Regulation of the Chief of Police. The technique of collecting legal materials carried out is by reviewing or analyzing laws and regulations, the 1945 Constitution, and other regulations. The results showed that (1) From the regulations related to the procedures for the implementation of the death penalty in Law No. 2 / PNPS / 1964 has not regulated the deadline for the implementation of the death penalty. It only regulates the extent of notification before execution, which is 3 x 24 hours. This uncertainty certainly creates legal uncertainty and will have an impact on the psychology of the convict. In Indonesia itself, regarding the time span after the judge's decision until he will actually be executed, in fact, it takes quite a long time. Because in casu laws and regulations do not regulate this. Regarding when the convict will be executed depends entirely on the policy of the prosecutor as executor. This cannot be done because the law in Indonesia should regulate in terms of material, formal, and implementation laws. (2) Regarding the inhibiting factors of the death penalty after the judge's decision, there are many such as statutory factors, law enforcement, and facilities. Therefore, it is necessary to regulate the implementation of the death penalty. Because the absence of this rule causes its own confusion for the community and also convicts sentenced to death. In addition, it is hoped that through the new Criminal Code, it is explained what conditions must be met by convicts so that the death penalty can be changed to a life sentence. Because when viewed from the existing rules, it is only explained related to the perpetrator's remorse and the perpetrator's relationship in criminal acts. If you only pay attention to these two factors, it is feared that in the future it will cause repeat crimes.